Morphological and molecular characterization of Fusarium spp. associated with Fusarium wilt disease of Piper nigrum L. in Northwestern region of Sarawak - Tan, Wan Joo; Vu Thanh, Tu Anh; Rafael, Elissa Stella; Chen, Yi Shang; Yeo, Freddy, Kuok San (Malaysian Society for Microbiology, 2021)
Aims: Piper nigrum L. (black pepper) is an economically important commodity plant in Malaysia, which generated RM200.95 million from pepper export in the year of 2018. However, the increase in pepper production is restricted by diseases. Fusarium wilt is one of the major diseases of P. nigrum L. The objectives for this study were to isolate Fusarium spp. associated with Fusarium wilt of P. nigrum L. from selected pepper farms in the northwestern region of Sarawak and to characterize the Fusarium spp. isolated morphologically and molecularly.